2010
DOI: 10.1186/1744-9081-6-62
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometric changes in the dorsal raphe neurons after rapid eye movement sleep deprivation are mediated by noradrenalin in rats

Abstract: ObjectivesThis study was carried out to investigate the effect of rapid eye movement sleep (REMS) deprivation (REMSD) on the cytomorphology of the dorsal raphe (DR) neurons and to evaluate the possible role of REMSD-induced increased noradrenalin (NA) in mediating such effects.MethodsRats were REMS deprived by the flowerpot method; free moving normal home cage rats, large platform and post REMS-deprived recovered rats were used as controls. Further, to evaluate if the effects were induced by NA, separate sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…The NA-induced effect, activation of the enzyme in the whole brain in this case, may be supported by the fact that the LC neurons have been reported to project throughout the brain (Samuels and Szabadi, 2008), and increased NA as well as TH mRNA have been reported in the rat brain after REMSD (Porkka-Heiskanen et al, 1995; Basheer et al, 1998). Also, it has been reported that in rat brains REMSD-induced changes in several enzyme activities (Thakkar and Mallick, 1991, 1993a,b; Amar and Mallick, 2015) and neuronal cytomorphology (Ranjan et al, 2010) are mediated by elevated level of NA.…”
Section: Discussionmentioning
confidence: 99%
“…The NA-induced effect, activation of the enzyme in the whole brain in this case, may be supported by the fact that the LC neurons have been reported to project throughout the brain (Samuels and Szabadi, 2008), and increased NA as well as TH mRNA have been reported in the rat brain after REMSD (Porkka-Heiskanen et al, 1995; Basheer et al, 1998). Also, it has been reported that in rat brains REMSD-induced changes in several enzyme activities (Thakkar and Mallick, 1991, 1993a,b; Amar and Mallick, 2015) and neuronal cytomorphology (Ranjan et al, 2010) are mediated by elevated level of NA.…”
Section: Discussionmentioning
confidence: 99%
“…Importance of REM sleep has been suggested by the study of Ranjan et al 29 who have concluded that REMSD could lead to neurodegeneration memory loss and Alzheimer’s disease. Sleep deprivation or prolonged wakefulness leads to decrements in cognitive performance, which is recognized as a major hazard to public safety and implicated in vehicular accidents, industrial catastrophes and other incidents involving error in human performance.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep has been divided into rapid eye movement sleep (REMS) and non-REMS, and as a common factor, at least the former is affected in most of the psychosomatic and neurodegenerative disorders. We have shown earlier that experimental REMS deprivation (REMSD) affects neuronal cytomorphology and structural protein leading to neuronal apoptosis and loss, and these effects were mediated by REMSD-associated elevation in the level of noradrenaline (NA) in the brain ( 1 3 ). Our contention gets supported by a recent report in humans that gray matter volume is reduced upon sleep disturbance ( 4 ).…”
Section: Introductionmentioning
confidence: 99%